The Effectiveness and Validity of Biomagz Based on the Museum Purbakala Sangiran in Evolutionary Learning in Senior High Schools (Journal of Biology Education, 2023)
This study aims to analyze the validity and analyze the effectiveness of Biomagz as a supplement to teaching materials on the evolutionary material of students in class XII of high school. Although the existence of teaching material sources in schools is complete, based on the explanations from students, teaching materials with an attractive appearance will motivate students to study harder. The development of biomagz is compiled based on observations made at the Museum Purbakala Sangiran which has the potential to be a source of learning, especially on evolutionary material. The development of biomagz based on the Sangiran Museum of Antiquities refers to basic competency standards in accordance with the 2013 curriculum, using Indonesian and designed as attractive as possible. The research was carried out with the aim of analyzing the characteristics of biomagz development, analyzing the validity and analyzing the effectiveness of biomagz as a supplement to teaching materials on the evolutionary material of class XII high school students. This research included R&D research. As many as 15 respondents of class XII MIPA 2 at SMA Negeri 2 Pekalongan were selected by random sampling in filling out the biomagz readability questionnaire. The effectiveness test stage was carried out at SMA Negeri 4 Pekalongan class XII MIPA 3 which amounted to 35 students with learning outcomes tests. The data collection method uses readability test questionnaires, tests and user response questionnaires. The data obtained based on the calendar and user response questionnaire can be analyzed with percentage descriptive techniques. The learning outcomes analyzed can then be compared with the expected percentage of classical completion. The results of the study showed that based on the results of the development of biomagz based on the Museum Purbakala Sangiran, it has characteristics including having an attractive appearance with a colored background, and presented with a variety of images obtained from the Sangiran Antiquities Museum. Biomagz was declared valid and had very decent criteria with media validation results of 93.6% and material validation of 84%. In addition, biomagz was also stated to be very good in the readability test and received a positive response from students and teachers on the results of the user's response to use. The percentage of student responses is 91% and the percentage of teacher responses the user's response to use. The percentage of student responses is 91% and the percentage of teacher responses is 95%. In addition, biomagz was declared effective because ≥85% of students had test scores above the standard score of KKM completion. The conclusion of the research is the characteristics of the development of biomagz as a supplement to student teaching materials based on the Sangiran Antiquities Museum which is interesting and can be used as a support for learning activities in the research process, biomagz based on the Sangiran Antiquities Museum is declared feasible as a supplement to evolutionary teaching materials, and biomagz is declared effective because ≥85% of students have test scores above the value of the drinking completion criteria or KKM. The supporting suggestion of this research is that the development of biomagz can be presented through a page that can be accessed by students anytime and anywhere.